Human mesenchymal stromal cells in adhesion to cell-derived extracellular matrix and titanium: Comparative kinome profile analysis - Baroncelli, Marta; Fuhler, Gwenny M.; van de Peppel, Jeroen; Zambuzzi, Willian F. [UNESP]; van Leeuwen, Johannes P.; van der Eerden, Bram C. J.; Peppelenbosch, Maikel P. (Wiley, 2019)
The extracellular matrix (ECM) physically supports cells and influences stem cell behaviour, modulating kinase-mediated signalling cascades. Cell-derived ECMs have emerged in bone regeneration as they reproduce physiological tissue-architecture and ameliorate mesenchymal stromal cell (MSC) properties. Titanium scaffolds show good mechanical properties, facilitate cell adhesion, and have been routinely used for bone tissue engineering (BTE). We analyzed the kinomic signature of human MSCs in adhesion to an osteopromotive osteoblast-derived ECM, and compared it to MSCs on titanium. PamChip kinase-array analysis revealed 63 phosphorylated peptides on ECM and 59 on titanium, with MSCs on ECM exhibiting significantly higher kinase activity than on titanium. MSCs on the two substrates showed overlapping kinome profiles, with activation of similar signalling pathways (FAK, ERK, and PI3K signalling). Inhibition of PI3K signalling in cells significantly reduced adhesion to ECM and increased the number of nonadherent cells on both substrates. In summary, this study comprehensively characterized the kinase activity in MSCs on cell-derived ECM and titanium, highlighting the role of PI3K signalling in kinomic changes regulating osteoblast viability and adhesion. Kinome profile analysis represents a powerful tool to select pathways to better understand cell behaviour. Osteoblast-derived ECM could be further investigated as titanium scaffold-coating to improve BTE.
Keywords: cell adhesion; extracellular matrix; kinome profiling; osteoblasts; titanium